The kinase domain of TRPM7 interacts with PAK1 and regulates pancreatic cancer cell epithelial-to-mesenchymal transition - Julie Auwercx; Bernadette Neve; Alison Vanlaeys; Mathilde Fourgeaud; Ingrid Bourrin-Reynard; Mouloud Souidi; Sylvie Brassart-Pasco; Frédéric Hague; Stéphanie Guenin; Belinda Duchene; Laurent Gutierrez; Olivier Destaing; et al. (Cell Death and Disease)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is the main and the deadliest form of pancreatic cancer. This is a major problem of public health since it will become the second leading cause of death by cancer in the next few years, mainly due to the lack of efficient therapies. Transient Receptor Potential Cation Channel Subfamily M Member 7 (TRPM7) protein, a cation channel fused with a serine/threonine kinase domain is overexpressed in PDAC and associated with a low survival. In this work, we aim to study the role of kinase domain on pancreatic cell fates by using a model of kinase domain deletion by CRISPR-Cas9. PANC-1 and MIA PaCa-2 PDAC cell lines were used and kinase domain was deleted by CRISPR-Cas9 strategy. Kinase domain deletion (ΔK) was validated by RT-qPCR and western blots. The effect of kinase domain deletion on channel function was studied by patch-clamp and Mn2+-quenching. The cell phenotype was studied by MTT and cell migration/invasion assays. Finally, the role of kinase domain was studied in vivo in xenografted mice. Here we show that TRPM7 kinase domain is required to maintain a mesenchymal phenotype in PDAC cells. We also demonstrated that TRPM7 and PAK1 interact in the same protein complexes. Moreover, TRPM7 kinase domain is required for carcinogenesis and cancer cell dissemination in vivo. Intriguingly, the role of TRPM7 kinase is cell specific and may depend on the KRAS oncogene mutation status. In conclusion, TRPM7 kinase domain is required to maintain a mesenchymal and aggressive phenotype in PDAC cells, and it could be a promising target against PDAC.